Marine sponge-associated bacteria as biocontrol agents of vibriosis on whiteleg shrimp caused by Vibrio parahaemolyticus - NEPTU ISLAMY RAHARJA; WIDANARNI; Aris Tri Wahyudi (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Raharja NI, Widanarni, Wahyudi AT. 2019. Marine sponge-associated bacteria as biocontrol agents of vibriosis on whiteleg shrimp caused by Vibrio parahaemolyticus. Biodiversitas 20: 3164-3169. Sponge-associated bacteria are commonly known as an excellent source of microbial's bioactive compounds attributed to biological properties, including antibacterial activity. In our previous study, 12 isolates from sponge Aaptos sp. and Hyrtios have been screened to have anti-Vibrio spp. activities in vitro. The objective of this study was to evaluate these bacterial isolates for controlling Vibrio parahaemolyticus infection in vivo, identify the most potential isolate, and analyze chemical composition of bacterial crude extract. As tested by pathogenicity assay on post-larvae of whiteleg shrimp stadia PL 10, all 12 isolates were not pathogenic bacteria as indicated by the survival rate of shrimps ranging from 80 ± 8.1 - 93 ± 4.7%. Conversely, more than 50% died after inoculated with pathogenic V. parahaemolyticus. Interestingly, all isolates could increase the survival rate of shrimps infected with V. parahaemolyticus (105 cells/mL) reach of 80 ± 0.8 - 91 ± 0.4%, nearly 40% higher than the positive control, as evaluated by challenge test. The best anti-Vibrio activity showed by D2.Z13 isolate which could improve the survival rate up to 91.11 ± 0.4%. 16S-rRNA-based identification showed that this isolate was closely related to Pseudomonas aeruginosa 1-4-b-9 strain. The extract derived from this isolate contained some major compounds such as 4,8-dihydroxy-2-2 (1’-hydroxyheptyl) and 1,2,4-oxadiazol which have been reported as antibacterial compounds. Our study indicates that these bacterial isolates could be developed as biocontrol agents of vibriosis in whiteleg shrimp.